Identification of Aspartic Acid Enantiomers Based on Molecularly Imprinted Polyaniline - 孔泳 姚超 倪珺华 周永生 陈智栋 (Chinese journal of chemistry, 2011)
Affinity sites for L-aspartic acid （L-Asp） in polyaniline （PAn） were created by two successive processes： first, L-Asp was simply added as template molecules during the polymerization of aniline; second, L-Asp incorporated in PAn backbone was extracted by solvent. PAn with cavities complementary to L-Asp template molecules has been utilized for enantioselective recognition of L- and D-Asp. Enantioselectivity of the imprinted PAn could be attributed to the cavities in the imprinted PAn which was complementary to L-Asp templates both in shape and in positioning of groups. Also in this paper, the structural changes before and after extraction of L-Asp templates were revealed by Fourier-transform infrared （FTIR） spectrum.